The Analysis and modeling of widespread anomalies of rainfall in entire West of Iran in relation with the behaviors of Mediterranean Pressure centers - Faramarz khoshakhlagh; mohammad amin heydary (تحقیقات کاربردی علوم جغرافیایی)
Climate control centers in each area are diverse and understanding how they relate to the atmospheric components of the Earth's surface contribute to prediction of climate fluctuations.   In this study, by using Pearson's correlation and multivariate regression in a thirty-year period (1961-2010), the relationship between widespread rainfall anomalies in entire of Iran west with temperature and pressure of atmospheric centers in East and West of Mediterranean Sea in 5 atmospheric levels (SLP, 850, 500 and 300 Hpa) were analyzed and modeled. Based on the results, the correlation of atmospheric control centers in the East and West Mediterranean Sea with anomalies of rainfall in West of Iran is inverse and meaningful in 95% level. In this study, statistical indicators such as temperature differences and standardized  pressure between West and East Mediterranean sea were identified as the most important indicators in relation to changes of rainfall in the study area.   Based on the designed indicators, whenever indicators DT and DH is positive, this means higher temperature and higher atmospheric standardized pressure in the Western parts of Mediterranean sea in compare with its East and therefore the wet spells (Monthly) occur in the study area, and If the above mentioned index is negative, means that the occurrence of drought in West Iran. As for the indicators introduced for lower levels of the atmosphere, especially in the case of temperature, meaningful strong and direct correlation is seen with rainfall abnormalities in entire West of Iran. Modeling provided some indicator for Mediterranean region using multivariate regression that they showed a relatively strong correlation in this regard of the selected components that include the pressure difference in sea level, the temperature difference in 925 and 850 hPa level in the West (Compared to its East) Mediterranean sea. Also check the regression model using real data confirm the accuracy of the relative performance of the model.